2011
DOI: 10.1111/j.1364-3703.2011.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications of flow cytometry in plant pathology for genome size determination, detection and physiological status

Abstract: Flow cytometers are probably the most multipurpose laboratory devices available. They can analyse a vast and very diverse range of cell parameters. This technique has left its mark on cancer, human immunodeficiency virus and immunology research, and is indispensable in routine clinical diagnostics. Flow cytometry (FCM) is also a well-known tool for the detection and physiological status assessment of microorganisms in drinking water, marine environments, food and fermentation processes. However, flow cytometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 121 publications
(167 reference statements)
1
27
0
1
Order By: Relevance
“…Despite the common use of FCM for the measurement of genome size in plants and animals, the application of this technique in fungi has been minimal. The genome size measurement of fungi is relatively difficult, as they often have complicated life cycles with ploidy levels ranging from 1 × to 50 × and the basic chromosome numbers are often unknown (D'Hondt et al ., ). Moreover, in rust fungi with thick‐walled spores, such as H. vastatrix , this morphological characteristic represents a crucial technical problem for obtaining sufficient nuclei for FCM analyses because isolated nuclei have to be used for the stoichiometric staining reaction and the DNA quantitative measurements.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Despite the common use of FCM for the measurement of genome size in plants and animals, the application of this technique in fungi has been minimal. The genome size measurement of fungi is relatively difficult, as they often have complicated life cycles with ploidy levels ranging from 1 × to 50 × and the basic chromosome numbers are often unknown (D'Hondt et al ., ). Moreover, in rust fungi with thick‐walled spores, such as H. vastatrix , this morphological characteristic represents a crucial technical problem for obtaining sufficient nuclei for FCM analyses because isolated nuclei have to be used for the stoichiometric staining reaction and the DNA quantitative measurements.…”
Section: Discussionmentioning
confidence: 70%
“…(), the nuclear content of the standard should be similar to that of the sample being analysed. The current study adopted this strategy by using S. lycopersicum , because there are no stable and well‐characterized fungal internal standards (D'Hondt et al ., ). In fact, as shown by Bennett et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome size in Eukaryotes varies greatly, as a result of polyploidization and/or structural chromosomal rearrangements. Genome size and its dynamics have direct implications on the evolutionary fitness, reproduction and non-sexual mechanisms for diversity creation (D'Hondt et al, 2011). Among Fungi, previous studies have revealed that genomes vary from <1 to 893 Mbp (Kullman et al, 2005;Tavares et al, 2014).…”
mentioning
confidence: 99%